ON C. S. PEIRCE´S PRIMARY ARITHMETIC - Garnica, Antonio Vicente Marafioti [UNESP]; de Souza, Leandro Josué [UNESP]; Salandim, Maria Ednéia Martins [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2020)
This paper presents the initial studies on Peirce´s Primary Arithmetic, a set of manuscripts, never published by the author, written at the end of the XIX century. The originals – organized and published by Carolyn Eisele in 1976 – was translated to Portuguese and some initial studies are being developed focusing on the possibility that some features of Peirce´s Philosophy could be pragmatically – but implicitly – present in such manuscripts. Our partial conclusions, now, show that Peirce´s life circumstances, more than his Philosophy, characterize the texts under examination.
SOBRE A ARITMÉTICA ELEMENTAR DE C. S. PEIRCE
Keywords: Charles S. Peirce; History; Mathematics Education; Peirce´s Mathematical Writings; Philosophy; Primary Arithmetic